Pengaruh Sosial Masyarakat Penggabungan Desa Marsada Kecamatan Sipirok Kabupaten Tapanuli Selatan - Abdul Ma`arif (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2026)
Law Number 32 of 2004 concerning Regional Government, Article 200 paragraph (2), states that the formation, abolition, and/or merger of villages must take into account their origins and be initiated by the community. This law is reinforced by Government Regulation Number 72 of 2005 concerning Villages, which mentions the formation and change of village status, and Regulation of the Minister of Home Affairs (Permendagri) Number 28 of 2006 concerning the formation, abolition, merger of villages, and the change of village status to sub-district. Based on this, the Sipirok District Government, which is part of South Tapanuli Regency, also implements the mandate of these Regional Regulations. Most villages in Sipirok District have been merged to form new villages, and some have had their status changed to sub-districts. The research method used was qualitative research. The results indicate several advantages and disadvantages of village mergers for social, administrative, and governmental purposes.